The Use of Application Letter Resources on Improving Writing Competence Students at SMA Istiqamah Bandung - Khadafi, Muhammad Hilvan; Gumelar, Wahyu Satya (Universitas Nusantara PGRI Kediri, 2024)
Writing is a means of expressing thoughts and emotions. Writing is a serves as a way for individuals to communicate with their surroundings, especially for students in senior high school. Writing is employed in all learning activities. One of the activities students engage in is writing descriptive texts. Students are required to communicate effectively in English, orally and in writing. Proficiency in writing is essential before students can speak English fluently. It is expected that students can write effectively and accurately, as writing is crucial for their success in learning English. This study aims to enhance students writing skills through the use of application letters. By engaging with application letters, students are guided to assess their writing competencies and improve their skills, particularly among third-grade students in XII IPA 2 senior high school. This research employed a qualitative approach involving observation, questionnaires, and interviews. The study included 28 third-grade students from XII IPA 2 senior high school as participants. The findings indicate that the use of application letters has effectively enhanced students' writing competencies. It is recommended that students gain confidence in expressing their ideas in written form and utilize application letters to overcome writing difficulties and find solutions.